William Edmund Curtis papers - Curtis, William Edmund, 1855-1923.
Correspondence, memoranda, notes, reports, codebooks, financial papers, newspaper clippings, printed material, scrapbooks, and other papers relating chiefly to Curtis's service as assistant secretary of the U.S. Dept. of the Treasury. Subjects include silver certificates, gold reserves, deficit spending, loans, custom receipts, inflation, and Curtis's daily life. Correspondents include Alvey A. Adee, John Griffin Carlisle, F. Marion Crawford, Charles S. Fairchild, Hickson W. Field, Richard Watson Gilder, Sir Edward Goschen, Sir Hugh Henry Gough, Sir Alan Johnstone, C. N. Jordan, Joseph S. McCoy, Maurice L. Muhleman, William Alfred Peffer, J. G. Rosengarten, James Joseph Speyer, and James Stillman.
Assistant secretary of the U.S. Dept. of the Treasury.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adee, Alvey A. -- 1842-1924 -- Correspondence; Carlisle, John Griffin, -- 1835-1910 -- Correspondence; Crawford, F. Marion -- 1854-1909 -- Correspondence; Fairchild, Charles S. -- 1842-1924 -- Correspondence; Field, Hickson W. -- 1823- -- Correspondence; Gilder, Richard Watson, -- 1844-1909 -- Correspondence; Goschen, Edward, -- Sir, -- 1847-1924 -- Correspondence; Gough, Hugh Henry, -- Sir, -- 1833-1909 -- Correspondence; Johnstone, Alan, -- Sir -- Correspondence; Jordan, C. N. -- Correspondence; McCoy, Joseph S. -- Correspondence; Muhleman, Maurice L. -- 1852-1913 -- Correspondence; Peffer, William Alfred, -- 1831-1912 -- Correspondence; Rosengarten, J. G. -- 1835-1921 -- Correspondence; Speyer, James, -- 1861-1941 -- Correspondence; Stillman, James, -- 1850-1918 -- Correspondence; United States. -- Department of the Treasury; Customs administration -- United States; Deficit financing -- United States; Gold standard; Government lending -- United States; Inflation (Finance) -- United States; Silver question; United States -- Economic policy; Public officials